Selection of process parameters in a single-pass laser bending process. Issue 9 (2nd September 2018) - Kumar, Vikash; Dixit, Uday S.
ABSTRACT: In this article, a strategy for the optimum selection of laser process parameters, namely, scan speed, power and beam diameter, is presented that considers not only the accuracy of laser bending, but also the residual stresses, the maximum temperature along with temperature-affected zone, radius of bend, energy consumption and production rate. Performance is predicted by means of a three-dimensional thermoelastic–plastic finite element model, incorporating certain features to make it computationally efficient. In addition, an empirical model is used for the quick prediction of the maximum temperature, which helps in reducing the number of time-consuming runs of the finite element model. As the optimization of the process is multi-objective in nature, a fuzzy-set based strategy is suggested for a higher level decision. The efficacy of the procedure is demonstrated through examples and in-house experiments.